Antimony accumulation and iron plaque formation at different growth stages of rice (Oryza sativa L.). (June 2019) - Long, Jiumei; Tan, Di; Deng, Sihan; Li, Bingyu; Ding, Dan; Lei, Ming
Abstract: To better understand the Sb phytoavailability in rice, we studied Sb accumulation in rice (Zhongjiazao-17, widely cultivated in Hunan province) at different growth stages based on adding Sb III and Sb V to waterlogged soils in 10, 50 and 100 mg kg −1 treatment levels. Proportional exogenous Sb III and Sb V remained in the soil solution after equilibration. In Sb III treatments, the iron plaque (IP) amounts and Sb in rice roots sharply increased from tillering to jointing stages and then reduced at the following stages. However, in Sb V treatments, they increased continuously from tillering to maturing stages. The accumulation trends of Sb in straws, ears and grains were consistent in Sb III and Sb V treatments, rising from tillering to jointing stages followed with reducing from jointing to flowering stages slightly, and rising again significantly from flowering to maturing stages. The Tfsoil-grain values in all the Sb treatments were low (0.77 × 10 −3 -5.1 × 10 −3 ), However, when Sb in waterlogged soils were higher than 50 mg kg −1, it could pose human health risk for residents. Graphical abstract: Image 1 Highlights: Jointing stage is critical for Sb uptake in Sb III treatment. Flowering stage is critical for Sb uptake in Sb V treatment. Rice straw accumulated the highest concentration of Sb at maturing stage. Transfer ability of Sb decreased with increasing Sb treatment level. More than 50 mg kg −1 of Sb in soils is risky for residents. Abstract : Proportional of Sb III and Sb V still remained in soil solutions; The Sb accumulation trends at different rice growth stages were various.